PENGARUH RASIO LIKUIDITAS, RASIO PROFITABILITAS, INFLASI DAN NILAI TUKAR TERHADAP HARGA SAHAM (PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2023) - Yudistira, Aprilya; Putra, Hery Astika; Halpiah, Halpiah (Nusantara Hasana Journal, 2025)
The purpose of this study is to analyze the determinants that can show an influence on the share price of mining sector issuers, especially in Indonesia. The independent variables studied iclude liquidity ratio, profitability ratio, inflation and rupiah exchange rate, while the stock price serves as the criterion dependent variable. The study population consists of 73 mining sector entities that have been registered on the Indonesian capital market during the 2018 until 2023 period. Sample selection was carried out on 10 coal companies used the maximum variance sampling technique. Data analysis implements the multiple regression analysis with SPSS Platform version 26. This study findings indicate that each indicator of the liquidity ratio, inflation rate and currency exchange rate does not show a significant impact on stock price movements. However, the profitability ratio individually show a meaningful positive correlation to stock price valuation. Similarly, the result of simultaneously contribute significantly to the dynamics of changes in stock price of mining corporations registered on the Indonesia Stock Ecxhange.